(untitled) (European Journal of Child Development, Education and Psychopathology, 2021)
Reactive and proactive aggression are two of the main types of aggression identified in bullying. Some research suggests that self-control contributes to a decrease in proactive and reactive aggression. However, studies that have investigated the relationships of these variables with self-control in the Mexican context are scarce. The aim of this study was to explore the relationships between self-control with reactive and proactive aggression in Mexican adolescents. The sample was selected in a non-probabilistic way, the participants in this study were 300 adolescents with ages between 12 and 18 (M age = 14, SD = 1.55), 147 (49 %) were male, while 153 (51 %) were female. Self-control was measured with the subscale Values in Action Inventory of Strengths (VIA-Youth; Park & Peterson, 2006), for reactive and proactive aggression we use the Reactive and Proactive Aggression Questionnaire (QRP; Raine et al., 2006). Results indicate that self-control was negatively and significantly related to reactive and proactive aggression. This may indicate that adolescents with a higher level of self-control have a lower frequency of proactive aggression. this study contributes to understand the different types of aggression in school bullying in adolescents. In addition, the results suggest that self-control may decrease peer aggression.